Impact of Influencer Endorsement on Purchase Decision: Mediating Role of Brand Image and Moderating Effect of Customer Trust - Siahaan, Febri Sari; Beryansyah, Beryansyah; Purnawan, Lesna; Hasan, Raden; Priscillia, Amanda Sona (International Journal of Management and Digital Business, 2025)
This study examines the influence of influencer endorsement on purchase decisions for Sugarlab Face Mist products, with brand image as a mediator and customer trust as a moderator. Data were collected from 300 respondents in Jakarta and its surrounding areas, consisting of active social media users aged 18–40 years who have purchased products promoted by influencers. A purposive sampling technique was applied, and the analysis was conducted using a quantitative approach with Structural Equation Modeling based on Partial Least Squares (SEM-PLS) through Smart PLS 4.0 software. The results show that influencer endorsement significantly affects purchase decisions, both directly and through the mediation of brand image. A positive brand image strengthens consumers' purchase intentions and mediates the relationship between influencer endorsement and purchase decisions. Customer trust serves as a moderator that enhances the relationships between influencer endorsement, brand image, and purchase decisions. This study highlights the importance of influencer endorsement strategies in improving brand image and consumer purchase decisions.